QUEER AND NON-BINARY NARRATIVES IN YOUNG ADULT LITERATURE: TRENDS AND SOCIAL IMPACT - Achmad Zahruddin (INJOSEDU: International Journal of Social and Education, 2025)
The study of queer and non-binary narratives in young adult literature highlights the increasing representation of characters with diverse gender identities and sexual orientations. This literature reflects a cultural shift towards greater inclusivity, and offers more realistic depictions of the lives and challenges faced by queer and non-binary individuals. This research identifies that books in this genre not only fill a void in media representation, but also provide emotional and psychological support to young readers in search of identity. The social impact of this trend is significant, as it can reduce stigma, promote empathy, and encourage open conversations about gender identity and sexual orientation, ultimately creating a more inclusive and supportive society.